Optimization of a commercial hydro-isomerization process - Küçük, Ülfet Ece. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Isomerization process is one of the most commonly used processes in the petroleum refinery. Product of isomerization unit is “isomerate” that has a great importance for gasoline pool, since its research octane number (RON) is easy to be adjusted and it obeys the legislations about sulfur and benzene content of the gasoline pool. UOP PenexTM process is mostly used application for isomerization. PenexTM is created for the catalytic isomerization of low octane light straight run (LSR) naphtha to obtain high octane and branched isomers. Benzene reduction reactions also occur in the unit, product can be obtained with high octane number and low benzene content. In this thesis, the PenexTM unit at Tüpraş Izmir Refinery are operated at steady state, and optimized for given conditions. Optimization of the process is performed in HYSYS Optimizer Tool. Decision variables are determined after applying degree of freedom analysis to whole flow-sheet and constraints are determined by taking into account of top product rate and quality. Optimization is carried out in mixed mode, which is combination of both SQP and BOX methods, with nine decision variables and two constraints. Objective function of the process is chosen as maximum isomerate barrels production (maximum liquid yield). During the current study, catalyst of the PenexTM unit has been changed and difference between previous and current situation is investigated. The results show that, current state of the unit with changing 0.5-5 °C range of temperature for all unit elements, changing 180 m3/d of deisohexanizer column recycle rate and changing 35 ton/h of stabilizer overhead vapor rate gives optimized process with 85.5 RON and 4673 isomerate barrel value, for first condition. With the change of trickle bed catalyst, value of change in deisohexanizer recycle rate decreases 100 m3/d and change in stabilizer overhead vapor rate decreases 15 ton/h. Change in temperatures range remains constant for second condition. Also, in second condition, 87 RON and 5232 isomerate barrel value is obtained for optimized process.
Keywords: Isomerization.